Day 1 Wed, April 20, 2016 2016
DOI: 10.2118/180060-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Mechanisms During Low Salinity Waterflooding: Water Diffusion and Osmosis for Oil Mobilization

Abstract: This work study pore-level oil mobilization by water diffusion and osmosis during low salinity waterflooding using microscopic visualization in sandstone silicon-wafer micromodels. The twodimensional water-wet micromodels apply a high accuracy pore network with sharp edges and surface roughness to observe displacement processes during low salinity water injection. Residual and capillary trapped oil was mobilized when a salinity gradient between high-saline connate water in matrix and low salinity water flowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Sandengen and Arntzen (2013) suggested that the increase in the osmotic pressure causes brine expansion and oil displacement. This mechanism was agreed by Sandengen et al (2016), Fredriksen et al (2016), and Fredriksen et al (2017). However, Bartels et al (2017) showed that the osmosis pressure can contribute in the incremental oil recovery, but it is not the primary mechanism of LSWF.…”
Section: Introductionmentioning
confidence: 89%
“…Sandengen and Arntzen (2013) suggested that the increase in the osmotic pressure causes brine expansion and oil displacement. This mechanism was agreed by Sandengen et al (2016), Fredriksen et al (2016), and Fredriksen et al (2017). However, Bartels et al (2017) showed that the osmosis pressure can contribute in the incremental oil recovery, but it is not the primary mechanism of LSWF.…”
Section: Introductionmentioning
confidence: 89%
“…To evaluate the potential of nanoparticles as novel EOR agents, some studies have been performed on silica (SiO 2 ) nanoparticles dispersed in deionized water using a glass micromodel as a synthetic porous media (El-Diasty 2015; Gharibshahi et al 2015;Heydarian et al 2012;Li et al 2016;Maghzi et al 2012;Mohammadi et al 2012;Ragab and Hannora 2015;Salem Ragab and Hannora 2015). Likewise, many others have investigated LSE in the micromodel (Bondino et al 2013;Sohrabi 2012, 2013;Fredriksen et al 2016;Maaref et al 2017;Song and Kovscek 2015;Wei et al 2017). In light of those studies, one could conceive the question of how much would the benefit be of utilizing LSW augmented by nanoparticles?…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that the "dewetting patterns" mentioned by Bartels et al could be the water micro-droplets formed spontaneously when crude oil is gently contacted with water. S. B. Fredriksen et al 24,25 explained that oil can be displaced and mobilized by diffusion and osmosis. They studied, at pore scale level, the displacement of oil in presence of a salt concentration gradient.…”
Section: Introductionmentioning
confidence: 99%